Extraction, characterization of aloe polysaccharides and the in-depth analysis of its prebiotic effects on mice gut microbiota. (1st June 2021) - Liu, Chang; Du, Peng; Guo, Yahui; Xie, Yunfei; Yu, Hang; Yao, Weirong; Cheng, Yuliang; Qian, He
Graphical abstract: Highlights: A major part of APs consisted of → 4)-β-Man p -(1 → residues with acetyl groups. APs increased the concentration of SCFAs in mice feces. Parabacteria and Clostridium were the key microbiota to degrade APs. APs up-regulated the expression of fructose-bisphosphate aldolase [EC:4.1.2.13]. Abstract: Despite the well-known health benefits of aloe polysaccharide (APs), little is known about how APs modulate the gut microbiota and the relationship between microbiota and SCFAs. Here, APs was extracted by ultrasound extraction. FT-IR and glycosidic linkage type analysis showed that a major part of APs consisted of → 4)-β-Man p -(1 → residues with acetyl groups. APs supplementation to mice prominently boosted SCFAs-producing Bacteroides and Parabacteria in the feces. On the other hand, it decreased the abundance of Firmicutes and Clostridium . A positive correlation between microbiota and SCFAs was revealed, with Parabacteria and Clostridium being the key microbiota to significantly promote SCFAs. APs promoted the fructose and mannose metabolism by upregulating the gene expression of 17 enzymes, containing fructose-bisphosphate aldolase [EC:4.1.2.13]. Our findings highlight SCFAs-producing Parabacteria were primary degrader of APs, and APs may have prebiotic effects on gut microbiota.